Penggunaan Psikotropika pada Anak dan Remaja Penderita Asma di Belanda 1999-2006 - Aini, Siti Rahmatul (Jurnal Kedokteran, 2012)
Introduction: To determine the association between asthma and the use of psychotropic drugs by focusing on whether the asthmatic children receive more often psychotropic drugs compared with non asthmatic children in the population based cohort design. Method: Using InterAction Database (IADB), drug dispensing data from Dutch community pharmacies (55 community pharmacies) in 1999 – 2006, children and adolescents aged 0 to 19 years in the study period (1 Januari 1999 to 31 Desember 2006 were divided into two groups; the index (asthmatic children and adolescents) and the reference (antibiotic children and adolescents) groups. We calculated the incidences of psychotropic drugs use (in both groups) and the incidence risk ratio (IRR). Results: The incidences of psychotropic drug use were 0.058 cases/1000 person-days in index group and 0.048 cases/1000 person-days in reference group. The incidence risk ratio of anti psychotropic drug use was 1.21 ( CI 1.18-1.29). Conclusions : Asthmatic patients are 1.21 times more likely than non asthmatic patients to receive psychotropic drugs over the 8 years period in this study.